"Conditional PPP" and real exchange rate convergence in the euro area. (May 2017) - Bergin, Paul R.; Glick, Reuven; Wu, Jyh-Lin
Highlights: Real exchange rate convergence is estimated before and after monetary union. Real exchange rates converge faster after countries joined the euro currency union. Flexible exchange rates can promote adjustment or be a source of shocks. Flexible exchange rates are not necessary to long-run relative price adjustment. Abstract: While economic theory highlights the usefulness of flexible exchange rates in promoting adjustment in international relative prices, flexible exchange rates also can be a source of destabilizing shocks. We find that when countries joining the euro currency union abandoned their national exchange rates, the adjustment of real exchange rates toward their long-run equilibrium surprisingly became faster. To investigate, we distinguish between differing rates of purchasing power parity (PPP) convergence conditional on alternative shocks, which we refer to as "conditional PPP." We find that the loss of the exchange rate as an adjustment mechanism after the introduction of the euro was more than compensated by the elimination of the exchange rate as a source of shocks, in combination with faster adjustment in national prices. These findings support claims that flexible exchange rates are not necessary to promote long-run international relative price adjustment.